Meningkatkan Kemampuan Menyelesaikan Masalah Kontekstual dan Prestasi Belajar Matematika Melalui Discovery Learning Berbantuan LAS dan BAS - Warsiyanto, Warsiyanto (Universitas Muhammadiyah Magelang, 2020)
This study aims to improve the ability to solve contextual problems and mathematics learning achievement through the application of discovery learning models with cooperative learning background assisted by LAS and BAS media. This Classroom Action Research was conducted in class IXA of SMP Negeri 2 Banjarnegara in the academic year 2019/2020. Subjects were 32 students, 14 male and 18 female. The study was conducted in 2 cycles with procedures: a) planning; b) implementation; c) observation; d) reflection. Data collection techniques with observation and tests. Data analysis techniques using qualitative descriptive methods and descriptive statistics. The results showed increased ability, students who have high and very high categories from 25% to 68.76% then 90.625%. Learning achievement increased from an average of 74.5 to 86.34 and finally 90.53 or (21.52%) and mastery learning increased from 65.63% (21 students) to 87.5% (28 students) and finally 100 % (32 students) or increased 33.33% from the beginning to the end. The results of this study are expected to be useful for teachers to reference their learning innovations, for schools to facilitate teacher learning in an effort to improve student learning achievement.